Targeting specific molecular pathways holds promise for advanced gallbladder cancer therapy. Issue 3 (March 2015) - Bizama, Carolina; García, Patricia; Espinoza, Jaime A.; Weber, Helga; Leal, Pamela; Nervi, Bruno; Roa, Juan Carlos
Highlights Advanced gallbladder cancer has poor prognosis and inherent resistance to adjuvant therapy. The genetic and epigenetic alterations play an important role in gallbladder carcinogenesis. Emergent signaling pathways in GBC must be explored in order to design rational therapies. The use the inhibitors of oncogenic pathways is a promising therapeutic alternative in GBC.